Appendiceal Intussusception Mimicking Cecal Mass and Fecal Matter: A Report of Two Rare Cases - James Haug; AS Katkar; James Covelli (Case Reports in Radiology)
Intussusception of the appendix is a relatively rare event that is usually asymptomatic but can present similar to other acute and chronic abdominal conditions. We present two separate cases of suspected appendiceal intussusception mimicking cecal masses. The authors also present a cursory review of the limited number of literatures available concerning this entity to help the radiologist avoid misdiagnosis and potentially unnecessary invasive intervention.